Measuring organized crime: an international perspective - Savona, Ernesto Ugo (Improving knowledge on crime, 2009)
The present article, the first of a series of three articles by the same author that appear in the present issue, contains a review of current approaches to the measurement of organized crime with a focus on key global and national studies. The author introduces the principles behind the measurement of organized crime from an international perspective. International comparisons of the risk of organized crime can assist policymakers in combating that phenomenon.